Dual Intra-Articular Fracture of the Body and Hook of Hamate: A Delayed Presentation - Eimear Phoenix; John Mahon; Robert M. Kenyon; Rafal Pajda (Case Reports in Surgery)
Fractures of the hamate bone are an unusual clinical entity. Dual fractures involving both the body and the hook of the hamate are even more unique, with only two previous cases described in the literature, to our knowledge. Clinicians are often unfamiliar with the presenting signs of this unusual injury, and subsequently, diagnosis is often delayed or missed entirely. We describe the case of a 19-year-old male who sustained an intra-articular body of hamate fracture with an ipsilateral hook of hamate fracture in his dominant hand. He presented 10 days following the initial injury and was managed with open reduction and internal fixation (ORIF).